A study on the level of customer satisfaction towards tangible facilities in Melaka River Pirate Park / Muhammad Hasif Sulaiman, Nursyafiqah Harris Fadilah and Siti Masturah Ayu Mohd Fauzi - Sulaiman, Muhammad Hasif; Harris Fadilah, Nursyafiqah; Mohd Fauzi, Siti Masturah Ayu (Faculty of Hotel and Tourism Management, 2013)
The theme park industry has experienced steady growth for many years, and it has developed into a global phenomenon. Monitoring visitor satisfaction is critical to help ensure a satisfying overall experience, customer value, and repeat visits. Here, we examine customer satisfaction from the data collection in Melaka River Theme Park. The study focuses on identifying significant tangibility factor influencing customer evaluation and satisfaction with the overall theme park experience. The key findings reveal that visitors evaluate the theme park primarily on overall park experience based on the tangible facilties that the theme park provide. Core conditions amusement parks must meet are cleanliness and the presence of nice scenery. Other features vary in importance.